2000
DOI: 10.1007/s001170050846
|View full text |Cite
|
Sign up to set email alerts
|

Radiodiagnostik der Lunge

Abstract: Radiological cross-sectional imaging modalities, particularly computed tomography (CT) have become the mainstays for diagnosing lung disease in recent years. These enable morphological visualization of pathological processes with the greatest possible spatial resolution. Modern technical developments and complementary strategies have led to new applications and new functional assessments which need to be reviewed together with state-of-the-art techniques in nuclear imaging. The diagnosis of pulmonary embolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…CT is helpful in identifying pulmonary nodules, parenchymal diseases, and chest-wall involvement for superior sulcus tumors and lung disease. 55,56 Dynamic contrast-enhanced CT is the most sensitive study for the hepatic system. 57,58 MR is the gold standard for visualization of brain neoplasms and is increasingly used in SBRT applications including prostate, spinal tumors, chest, and solid abdominal tumors.…”
Section: Iva Simulation Imagingmentioning
confidence: 99%
“…CT is helpful in identifying pulmonary nodules, parenchymal diseases, and chest-wall involvement for superior sulcus tumors and lung disease. 55,56 Dynamic contrast-enhanced CT is the most sensitive study for the hepatic system. 57,58 MR is the gold standard for visualization of brain neoplasms and is increasingly used in SBRT applications including prostate, spinal tumors, chest, and solid abdominal tumors.…”
Section: Iva Simulation Imagingmentioning
confidence: 99%
“…Andererseits kommt es bei 0,4 bis 5% der Patienten nicht zu einer vollständigen Thrombolyse (Kauczor et al, 2000). Dann wird das thrombembolische Material in die Gefäßwand eingebaut mit der Folge einer bleibenden Reduktion des Gesamtquerschnittes der Pulmonalisstrombahn.…”
Section: Die Veränderungen Führen üBer Eine Reduktion Des Gefäßlumensunclassified
“…Other features of CT are the application of high‐resolution CT to detect lymphangitic carcinomatosis and the use of low dose CT for dose reduction. Recent studies have shown low‐dose spiral CT of the chest to be of high sensitivity in the detection of pulmonary nodules, making a dose minimization possible (42, 43).…”
Section: Pulmonary Metastasesmentioning
confidence: 99%
“…FDG‐PET represents an important and accurate tool for detecting and diagnosing neoplastic disease of the lung (43). Both FDG‐PET and Tc99m‐SPECT present a high degree of sensitivity, specificity and overall accuracy in the diagnostics of patients with a solitary pulmonary nodule suspected for metastatic disease (46) and in the differential of viable tumor tissue.…”
Section: Pulmonary Metastasesmentioning
confidence: 99%